Pengetahuan Tentang Rokok,Pusat Kendali Kesehatan Eksternal dan Perilaku Merokok - Chotidjah, Sitti (Makara Human Behavior Studies in Asia, 2012)
This study was to determine the effect of an external health locus of control on smoking behavior mediated by knowledge about smoking in adolescent boys. The sampling technique was accidental sampling. Subjects were 110 adolescents aged 15-20 years from Yogyakarta. Reliability test results demonstrate the scale of the external health locus of control has good reliability (α = 0.854), while a test of knowledge about smoking have KR-20 = 0.311 and scale α = 0.405 smoking behavior, which means that two instruments are less reliable. In addition, the research data did not meet the assumptions of normality (a = 0.005 < 0.05) and linearity that are required to analyze the data in path analysis. The test results with t-test showed that there were differences in external health locus of control (t = -0.913, p = 0.363; F = 1.360, p = 0.204 > 0.05) and knowledge related to smoking (t = 1.572, p = 0.119; F = 1, 276, p = 0.261 > 0.05) among regular and experiment smokers. Spearman correlation test results showed there is a correlation between smoking behavior with external health locus of control (rs = 0.210, p = 0.027 < 0.05) but there is nota correlation between smoking behavior with knowledge related to smoking (rs = 0.155, p = 0.105 > 0, 05).